Analysis of Profitability, Leverage, and Company Size on Tax-Avoidance - Mandasari, Pratika Intan; Mubarok, Akhmad Yasir; Dasman, Sunita; Syahwildan, Muhamad (Growth: Journal Management and Business, 2023)
This study aims to determine the effect of profitability, leverage, and company size on tax avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Taxes in Indonesia from year to year never reach the target, although in terms of nominal it has increased from year to year. The applicable tax collection in Indonesia is a self-assessment system, a system that requires taxpayers to calculate the amount of tax owed themselves. The weakness of this tax system is that it can lead to tax fraud and violations in the form of efforts to avoid or fight taxes (tax avoidance). The factors that cause companies to avoid paying taxes include: profitability, leverage and company size. This study uses a quantitative research approach, the type of secondary data obtained from the official website of the Indonesia Stock Exchange and the company concerned. Data analysis using descriptive analysis, panel data regression selection, followed by classical assumption test including normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The statistical method uses panel data regression analysis. The results show that profitability has a significant negative effect on tax avoidance, leverage has a significant effect on tax avoidance and company size has no effect on tax avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period.